2005
DOI: 10.1002/hep.20649
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells contribute to the impaired immune response in patients with chronic hepatitis B virus infection

Abstract: Chronic hepatitis B virus (HBV) infection is H epatitis B virus (HBV) is a common noncyto-pathic DNA virus. Infection with HBV in adults results frequently in a self-limiting, acute hepatitis, which confers protective immunity and causes no further disease. In 10% of infected adults, HBV leads to a chronic infection. Chronic HBV infection is an important risk factor for the development of cirrhosis and hepatocellular carcinoma. Worldwide, 350 million people suffer from chronic HBV infection, and approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
418
6
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 451 publications
(466 citation statements)
references
References 36 publications
34
418
6
5
Order By: Relevance
“…No obvious correlation was observed between ALT and HBV DNA in these patients. Earlier studies did not find a significant association between circulating CD4 ϩ CD25 ϩ Treg frequency and serum HBV DNA load in CHB patients (34,35). However, we observed that CHB patients with Ͼ10 7 copies/ml serum HBV DNA had a significant increase of circulating CD4 ϩ CD25 ϩ Treg compared with healthy controls.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…No obvious correlation was observed between ALT and HBV DNA in these patients. Earlier studies did not find a significant association between circulating CD4 ϩ CD25 ϩ Treg frequency and serum HBV DNA load in CHB patients (34,35). However, we observed that CHB patients with Ͼ10 7 copies/ml serum HBV DNA had a significant increase of circulating CD4 ϩ CD25 ϩ Treg compared with healthy controls.…”
Section: Discussioncontrasting
confidence: 81%
“…This result is identical to the data from Bertoletti's group (34), but differs from the data from Janssen's group (35). A difference in methods, reagents, and samples used in the study might account for the discrepancies.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…T cells play an important role in chronic HBV infection. Indeed, several reports have reported an up-regulation of Tregs in chronic HBV infection [14][15][16][17] that were able to impair HBV-specific CD8? T cell function.…”
mentioning
confidence: 99%